Integrating the Sabbath, the Health Message, and Ubuntu as a Response to the Ecological Crises: A South African Seventh-day Adventist Perspective - Mqhayisa, Siyamthanda (Africa theological journal /published by the Faculty of Theology, Tumaini University Makumira, 2025)
This study is situated in the intersections between systematic theology and Christian ecotheology. It seeks to bring into dialogue the current ecological situation in South Africa with two Seventh-day Adventist beliefs, namely, the Sabbath and the health message in tandem with the African notion of ubuntu as a possibility of probing an ecological ethos and praxis in the Seventh-day Adventist church in the context of South Africa and beyond. On this basis, this paper offers an explication of the Seventh-day Adventist “Fundamental Beliefs,” the contributions that the Seventh-day Adventist church can make to Christian ecotheology, the South African situation and lastly the significance of the doctrine of the health message, Sabbath and ubuntu as response(s) to the current ecological crises. This study will contribute to the growth of ecotheology within the Seventh-day Adventist church in South Africa.